1990
DOI: 10.1007/bf01808275
|View full text |Cite
|
Sign up to set email alerts
|

Energy-rich glyceric acid oxygen esters: Implications for the origin of glycolysis

Abstract: The apparent Gibbs free energy change of hydrolysis (delta G degrees', pH 7) of the 2- and 3-O-glyceroyl esters of 2- and 3-O-L-glyceroyl-L-glyceric acid methyl ester were measured at 25 degrees C. The 2- and 3-glyceroyl esters were found to be 'energy-rich' with delta G degrees' values of -9.1 kcal mol-1 and -7.8 kcal mol, respectively. This result indicates that the analogous 2- and 3-glyceroyl esters of polyglyceric acid are also 'energy-rich' and, therefore, could have acted as an energy source for primiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Moreover, decreased levels of fructose and glyceric acid were also observed in the colon of THS-treated rats. Both of these metabolites are closely associated with the metabolism of glycolysis [33]. As stated above, DHAP isomerizes to the glyceraldehyde 3-phosphate and participates in the glycolytic pathway [28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, decreased levels of fructose and glyceric acid were also observed in the colon of THS-treated rats. Both of these metabolites are closely associated with the metabolism of glycolysis [33]. As stated above, DHAP isomerizes to the glyceraldehyde 3-phosphate and participates in the glycolytic pathway [28].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the lower part of glycolysis, from glyceraldehyde 3‐phosphate to pyruvate is universally conserved, and glyceraldehyde is one of the most attractive intermediates as an energy source for primitive organisms provided with nascent glycolysis. Some advantages of glyceraldehyde are: (a) it can be produced from formaldehyde under plausible prebiotic conditions [126–128]; (b) through glycolysis, it is an energy source for living purposes; (c) it is an important metabolite in photosynthesis; (d) it can be used in prebiotic condensation reactions [129,130]; and (e) it is a source of glycerol, necessary for synthesis of glycerolipids, the precursors of biomembranes.…”
Section: Is There a Mdr Ancestral Activity?mentioning
confidence: 99%
“…Life would not exist without these key molecules. Weber and Hsu have suggested that glyceraldehyde and glyceric acid esters could plausibly be the key molecules in the chemical evolution that led to earlier metabolic reactions [161,162]. Some of the characteristic features that make glyceraldehyde an ideal candidate for several metabolic pathways include its structural simplicity and plausible prebiotic synthesis from simple precursor such as formaldehyde as well as successful incorporation into various other chemical reactions to yield important biomolecules such as glycerol and energy-rich glycerol thioesters [163][164][165].…”
Section: A Few More Key Derivatives Of Glycerol Relevant To Origin Ofmentioning
confidence: 99%
“…The phosphorylated derivatives of these compounds are critical parts of metabolism. The prebiotic synthesis of phosphorylated derivatives of these compounds has been demonstrated [151][152][153][154][155][156][157][158][159][160][161][162][163][164], and these compounds serve as "feedstock" molecules to more complex sugars and macromolecules. Glycerol has also been demonstrated to serve as a backbone in synthetic nucleic acids as iso-GNAs [169][170][171][172][173].…”
Section: Recapitulation and Closing Thoughtsmentioning
confidence: 99%